DESIGNING BUSINESS CANVAS MODEL AND ANALYSIS BUSINESS IN WARUNG DIMSUM - Nurhayat, Kartika (Dinasti International Journal of Management Science, 2020)
The development of culinary business is increasing in Indonesia, especially in big cities, making promising business opportunities. Warung dimsum are used as research objects for the application of Business Model Canvas. The research method uses quantitative descriptive. Data collection is done by interview. The results of the interview show that the Key Activity element is the strongest in the Warung Dimsum. Suggestion from research is that there is a need to develop channel elements to expand sales.